Special situations private equity: the yahoo case of a strategically repositioned asset - Busch, Luan Max Schaeber (2024)
The main objective of this research is to investigate and understand value generation in private equity transactions. Through a comprehensive literature review, we seek to elucidate fundamental concepts, theories, and empirical findings. This includes asset identification, strategic decision-making processes in crisis situations, and the broader implications of these transactions for the stakeholders involved. The subsequent research section focuses on constructing an academic case study around the acquisition of Yahoo by the investor Apollo, with a particular emphasis on investing in declining assets. Informed by insights from the literature review, this segment provides a detailed analysis of the factors necessitating turnaround for Yahoo and the strategic decisions made by Apollo to reposition this asset.